An Org-1-Tup transcriptional cascade reveals different types of alary muscles connecting internal organs in Drosophila - Boukhatmi, Hadi; Schaub, Christoph; Bataille, Laetitia; Reim, Ingolf; Frendo, Jean-Louis; Frasch, Manfred; Vincent, Alain (Development, 2014)
The T-box transcription factor Tbx1 and the LIM-homeodomain transcription factor Islet1 are key components in regulatory circuits that generate myogenic and cardiogenic lineage diversity in chordates. We show here that Org-1 and Tup, the Drosophila orthologs of Tbx1 and Islet1, are co-expressed and required for formation of the heart-associated alary muscles (AMs) in the abdomen. The same holds true for lineage-related muscles in the thorax that have not been described previously, which we name thoracic alary-related muscles (TARMs). Lineage analyses identified the progenitor cell for each AM and TARM. Three-dimensional high-resolution analyses indicate that AMs and TARMs connect the exoskeleton to the aorta/heart and to different regions of the midgut, respectively, and surround-specific tracheal branches, pointing to an architectural role in the internal anatomy of the larva. Org-1 controls tup expression in the AM/TARM lineage by direct binding to two regulatory sites within an AM/TARM-specific cis-regulatory module, tupAME. The contributions of Org-1 and Tup to the specification of Drosophila AMs and TARMs provide new insights into the transcriptional control of Drosophila larval muscle diversification and highlight new parallels with gene regulatory networks involved in the specification of cardiopharyngeal mesodermal derivatives in chordates.
Keywords: Tbx1; Org-1; Tup; Islet1; Alary muscle development; Transcriptional cascades; Drosophila

Bioassaying putative RNA-binding motifs in a protein encoded by a gene that influences courtship and visually mediated behavior in Drosophila: in vitro mutagenesis of nonA. - Stanewsky, Ralf; Fry, Thomas A.; Reim, Ingolf; Saumweber, Harald; Hall, Jeffrey C. (Genetics, 1996)
The no-on-transient-A (nonA) gene of Drosophila melanogaster influences vision, courtship song, and viability. The nonA-encoded polypeptide is inferred to bind single-stranded nucleic acids. Although sequence-analysis of NONA implies that it belongs to a special interspecific family of this protein type, it does contain two classical RNA recognition motifs (RRM). Their behavioral significance was assayed by generating transgenic strains that were singly or multiply mutated within the relatively N-terminal motif (RRM1) or within RRM2. Neither class of mutation affected NONA binding to polytene chromosomes. The former mutations led to extremely low viability, accompanied by diminished adult longevities that were much worse than for a nonA-null mutant, implying that faulty interpolypeptide interactions might accompany the effects of the amino-acid substitutions within RRM1. All in vitro-mutated types caused optomotor blindness and an absence of transient spikes in the electroretinogram. Courtship analysis discriminated between the effects of the mutations: the RRM2-mutated type generated song pulses and trains that tended to be mildly mutant. These phenotypic abnormalities reinforce the notion that nonA's ubiquitous expression has its most important consequences in the optic lobes, the thoracic ganglia, or both, depending in part on the nonA allele.

Cardioblast-intrinsic Tinman activity controls proper diversification and differentiation of myocardial cells in Drosophila - Zaffran, Stéphane; Reim, Ingolf; Qian, L; Lo, Patrick C; Bodmer, Rolf; Frasch, Manfred (Development, 2006)
The NK homeobox gene tinman (tin) is required for the specification of the cardiac, visceral muscle and somatic muscle progenitors in the early dorsal mesoderm of Drosophila. Like its vertebrate counterpart Nkx2.5, the expression of tin is maintained in cardiac cells during cardiac maturation and differentiation; however, owing to the complete lack of a dorsal vessel in tin mutant embryos, the function of tin in these cells has not been defined. Here we show that myocardial cells and dorsal vessels can form even though they lack Tin, and that viable adults can develop, as long as Tin is provided in the embryonic precardiac mesoderm. However, embryos in which tin expression is specifically missing from cardial cells show severe disruptions in the normal diversification of the myocardial cells, and adults exhibit severe defects in cardiac remodeling and function. Our study reveals that the normal expression and activity of Tin in four of the six bilateral cardioblasts within each hemisegment of the heart allows these cells to adopt a cell fate as 'working' myocardium, as opposed to a fate as inflow tract (ostial) cells. This function of tin involves the repression of Dorsocross (Doc) T-box genes and, hence, the restriction of Doc to the Tin-negative cells that will form ostia. We conclude that tin has a crucial role within myocardial cells that is required for the proper diversification, differentiation, and post-embryonic maturation of cardiomyocytes, and we present a pathway involving regulatory interactions among seven-up, midline, tinman and Dorsocross that establishes these developmental events upon myocardial cell specification.
Keywords: dorsal vessel; Drosophila; tinman; Dorsocross; Nkx2.5; seven-up; heart; repressor

Cbl-Associated Protein CAP contributes to correct formation and robust function of the Drosophila heart tube - Jammrath, Jennifer; Reim, Ingolf; Saumweber, Harald (PLoS ONE, 2020)
The formation of a tube-like structure is a basic step in the making of functional hearts in vertebrates and invertebrates and therefore, its understanding provides important information on heart development and function. In Drosophila, the cardiac tube originates from two bilateral rows of dorsally migrating cells. On meeting at the dorsal midline, coordinated changes in cell shape and adhesive properties transform the two sheets of cells into a linear tube. ECM and transmembrane proteins linked to the cytoskeleton play an important role during these dynamic processes. Here we characterize the requirement of Cbl-Associated Protein (CAP) in Drosophila heart formation. In embryos, CAP is expressed in late migrating cardioblasts and is located preferentially at their luminal and abluminal periphery. CAP mutations result in irregular cardioblast alignment and imprecisely controlled cardioblast numbers. Furthermore, CAP mutant embryos show a strongly reduced heart lumen and an aberrant shape of lumen forming cardioblasts. Analysis of double heterozygous animals reveals a genetic interaction of CAP with Integrin-and Talin-encoding genes. In post-embryonic stages, CAP closely colocalizes with Integrin near Z-bands and at cell-cell contact sites. CAP mutants exhibit a reduced contractility in larval hearts and show a locally disrupted morphology, which correlates with a reduced pumping efficiency. Our observations imply a function of CAP in linking Integrin signaling with the actin cytoskeleton. As a modulator of the cytoskeleton, CAP is involved in the establishment of proper cell shapes during cardioblast alignment and cardiac lumen formation in the Drosophila embryo. Furthermore, CAP is required for correct heart function throughout development.
CRIS-Team Scopus Importer:2020-06-16

Cis-regulatory chromatin loops arise before TADs and gene activation, and are independent of cell fate during early Drosophila development - Espinola, Sergio Martin; Götz, Markus; Bellec, Maelle; Messina, Olivier; Fiche, Jean Bernard; Houbron, Christophe; Dejean, Matthieu; Reim, Ingolf; Cardozo Gizzi, Andrés M.; Lagha, Mounia; Nollmann, Marcelo (Nature Genetics, 2021)
Acquisition of cell fate is thought to rely on the specific interaction of remote cis-regulatory modules (CRMs), for example, enhancers and target promoters. However, the precise interplay between chromatin structure and gene expression is still unclear, particularly within multicellular developing organisms. In the present study, we employ Hi-M, a single-cell spatial genomics approach, to detect CRM–promoter looping interactions within topologically associating domains (TADs) during early Drosophila development. By comparing cis-regulatory loops in alternate cell types, we show that physical proximity does not necessarily instruct transcriptional states. Moreover, multi-way analyses reveal that multiple CRMs spatially coalesce to form hubs. Loops and CRM hubs are established early during development, before the emergence of TADs. Moreover, CRM hubs are formed, in part, via the action of the pioneer transcription factor Zelda and precede transcriptional activation. Our approach provides insight into the role of CRM–promoter interactions in defining transcriptional states, as well as distinct cell types.
CRIS-Team Scopus Importer:2021-04-16

Distinct functions of the laminin beta LN domain and collagen IV during cardiac extracellular matrix formation and stabilization of alary muscle attachments revealed by EMS mutagenesis in Drosophila - Hollfelder, Dominik; Frasch, Manfred; Reim, Ingolf (Bmc Developmental Biology, 2014)
Conclusions: Assembly of the cardiac ECM depends primarily on laminin, whereas collagen IV is needed for stabilization. Our data underscore the importance of a correctly assembled ECM particularly for the development of cardiac tissues and their lateral connections. The mutational analysis suggests that the beta 6/beta 3/beta 8 interface of the laminin beta LN domain is highly critical for formation of contiguous cardiac ECM layers. Certain mutations in the collagen IV triple helix-forming domain may exert a semi-dominant effect leading to an overall weakening of ECM structures as well as intracellular accumulation of collagen and other molecules, thus paralleling observations made in other organisms and in connection with collagen-related diseases.
Keywords: Extracellular matrix; Heart tube; Alary muscles; Laminin; Collagen

Diversification of heart progenitor cells by EGF signaling and differential modulation of ETS protein activity - Schwarz, Benjamin; Hollfelder, Dominik; Scharf, Katharina; Hartmann, Leonie; Reim, Ingolf (eLife, 2018)

Expression, regulation, and requirement of the toll transmembrane protein during dorsal vessel formation in Drosophila melanogaster - Wang, JB; Tao, Y; Reim, Ingolf; Gajewski, K; Frasch, Manfred; Schulz, Robert A (Molecular and Cellular Biology, 2005)
Early heart development in Drosophila and vertebrates involves the specification of cardiac precursor cells within paired progenitor fields, followed by their movement into a linear heart tube structure. The latter process requires coordinated cell interactions, migration, and differentiation as the primitive heart develops toward status as a functional organ. In the Drosophila embryo, cardioblasts emerge from bilateral dorsal mesoderm primordia, followed by alignment as rows of cells that meet at the midline and morph into a dorsal vessel. Genes that function in coordinating cardioblast organization, migration, and assembly are integral to heart development, and their encoded proteins need to be understood as to their roles in this vital morphogenetic process. Here we prove the Toll transmembrane protein is expressed in a secondary phase of heart formation, at lateral cardioblast surfaces as they align, migrate to the midline, and form the linear tube. The Toll dorsal vessel enhancer has been characterized, with its activity controlled by Dorsocross and Tinman transcription factors. Consistent with the observed protein expression pattern, phenotype analyses demonstrate Toll function is essential for normal dorsal vessel formation. Such findings implicate Toll as a critical cell adhesion molecule in the alignment and migration of cardioblasts during dorsal vessel morphogenesis.

Genetic and Genomic Dissection of Cardiogenesis in the Drosophila Model - Reim, Ingolf; Frasch, Manfred (Pediatric Cardiology, 2010)
The linear heart tube of the fruit fly Drosophila has served as a very valuable model for studying the regulation of early heart development. In the past, regulatory genes of Drosophila cardiogenesis have been identified largely through candidate approaches. The vast genetic toolkit available in this organism has made it possible to determine their functions and build regulatory networks of transcription factors and signaling inputs that control heart development. In this review, we summarize the major findings from this study and present current approaches aiming to identify additional players in the specification, morphogenesis, and differentiation of the heart by forward genetic screens. We also discuss various genomic and bioinformatic approaches that are currently being developed to extend the known transcriptional networks more globally which, in combination with the genetic approaches, will provide a comprehensive picture of the regulatory circuits during cardiogenesis.
Keywords: Drosophila; Heart; Development

HLH54F is required for the specification and migration of longitudinal gut muscle founders from the caudal mesoderm of Drosophila - Ismat, A; Schaub, Christoph; Reim, Ingolf; Kirchner, Katharina; Schultheis, Dorothea; Frasch, Manfred (Development, 2010)
HLH54F, the Drosophila ortholog of the vertebrate basic helix-loop-helix domain-encoding genes capsulin and musculin, is expressed in the founder cells and developing muscle fibers of the longitudinal midgut muscles. These cells descend from the posterior-most portion of the mesoderm, termed the caudal visceral mesoderm (CVM), and migrate onto the trunk visceral mesoderm prior to undergoing myoblast fusion and muscle fiber formation. We show that HLH54F expression in the CVM is regulated by a combination of terminal patterning genes and snail. We generated HLH54F mutations and show that this gene is crucial for the specification, migration and survival of the CVM cells and the longitudinal midgut muscle founders. HLH54F mutant embryos, larvae, and adults lack all longitudinal midgut muscles, which causes defects in gut morphology and integrity. The function of HLH54F as a direct activator of gene expression is exemplified by our analysis of a CVM-specific enhancer from the Dorsocross locus, which requires combined inputs from HLH54F and Biniou in a feed-forward fashion. We conclude that HLH54F is the earliest specific regulator of CVM development and that it plays a pivotal role in all major aspects of development and differentiation of this largely twist-independent population of mesodermal cells.
Keywords: bHLH proteins; Cell migration; Mesoderm; Specification; Visceral muscles; Drosophila

Identification of the essential protein domains for Mib2 function during the development of the Drosophila larval musculature and adult flight muscles - Acs, Andreas; Obermeier, Claudia; Nguyen, Hanh; Reim, Ingolf; Domsch, Katrin (PLoS ONE, 2017)
The proper differentiation and maintenance of myofibers is fundamental to a functional musculature. Disruption of numerous mostly structural factors leads to perturbations of these processes. Among the limited number of known regulatory factors for these processes is Mind bomb2 (Mib2), a muscle-associated E3 ubiquitin ligase, which was previously established to be required for maintaining the integrity of larval muscles. In this study, we have examined the mechanistic aspects of Mib2 function by performing a detailed functional dissection of the Mib2 protein. We show that the ankyrin repeats, in its entirety, and the hitherto uncharacterized Mib-specific domains (MIB), are important for the major function of Mib2 in skeletal and visceral muscles in the Drosophila embryo. Furthermore, we characterize novel mib2 alleles that have arisen from a forward genetic screen aimed at identifying regulators of myogenesis. Two of these alleles are viable, but flightless hypomorphic mib2 mutants, and harbor missense mutations in the MIB domain and RING finger, respectively. Functional analysis of these new alleles, including in vivo imaging, demonstrates that Mib2 plays an additional important role in the development of adult thorax muscles, particularly in maintaining the larval templates for the dorsal longitudinal indirect flight muscles during metamorphosis.

Interdependence of PRC1 and PRC2 for recruitment to Polycomb Response Elements - Kahn, Tatyana G.; Dorafshan, Eshagh; Schultheis, Dorothea; Zare, Aman; Stenberg, Per; Reim, Ingolf; Pirrotta, Vincenzo; Schwartz, Yuri B. (Nucleic Acids Research, 2016)
Polycomb Group (PcG) proteins are epigenetic repressors essential for control of development and cell differentiation. They form multiple complexes of which PRC1 and PRC2 are evolutionary conserved and obligatory for repression. The targeting of PRC1 and PRC2 is poorly understood and was proposed to be hierarchical and involve tri-methylation of histone H3 (H3K27me3) and/or monoubiquitylation of histone H2A (H2AK118ub). Here, we present a strict test of this hypothesis using the Drosophila model. We discover that neither H3K27me3 nor H2AK118ub is required for targeting PRC complexes to Polycomb Response Elements (PREs). We find that PRC1 can bind PREs in the absence of PRC2 but at many PREs PRC2 requires PRC1 to be targeted. We show that one role of H3K27me3 is to allow PcG complexes anchored at PREs to interact with surrounding chromatin. In contrast, the bulk of H2AK118ub is unrelated to PcG repression. These findings radically change our view of how PcG repression is targeted and suggest that PRC1 and PRC2 can communicate independently of histone modifications.

Org-1-Dependent Lineage Reprogramming Generates the Ventral Longitudinal Musculature of the Drosophila Heart - Schaub, Christoph; März, Johannes; Reim, Ingolf; Frasch, Manfred (Current Biology, 2015)
Only few examples of transdifferentiation, which denotes the conversion of one differentiated cell type to another [1], are known to occur during normal development, and more often, it is associated with regeneration processes [2-7]. With respect to muscles, dedifferentiation/redifferentiation processes have been documented during post-traumatic muscle regeneration in blastema of newts as well as during myocardial regeneration [8, 9]. As shown herein, the ventral longitudinal muscles of the adult Drosophila heart arise from specific larval alary muscles in a process that represents the first known example of syncytial muscle transdifferentiation via dedifferentiation into mononucleate myoblasts during normal development. We demonstrate that this unique process depends on the reinitiation of a transcriptional program previously employed for embryonic alary muscle development, in which the factors Org-1 (Drosophila Tbx1) and Tailup (Drosophila Islet1) are key components. During metamorphosis, the action of these factors is combined with cell-autonomous inputs from the ecdysone steroid and the Hox gene Ultrabithorax, which provide temporal and spatial specificity to the transdifferentiation events. Following muscle dedifferentiation, inductive cues, particularly from the remodeling heart tube, are required for the redifferentiation of myoblasts into ventral longitudinal muscles. Our results provide new insights into mechanisms of lineage commitment and cell-fate plasticity during development.

T-Box Genes in Drosophila Mesoderm Development - Reim, Ingolf; Frasch, Manfred; Schaub, Christoph (T-box Genes in Development and Disease, 2017)

Tbx20-related genes, mid and H15, are required for tinman expression, proper patterning, and normal differentiation of cardioblasts in Drosophila - Reim, Ingolf; Mohler, JP; Frasch, Manfred (Mechanisms of Development, 2005)
Tbx20-related T-box genes have been implicated in the regulation of heart development in several vertebrate species. In the present report, we demonstrate that a pair of genes representing Drosophila orthologs of Tbx20, midline (mid) and H15, have important functions during the development of the Drosophila equivalent of the heart, i.e. the dorsal vessel. We show that mid is among the earliest known genes that are specifically expressed in all cardioblasts during early embryogenesis, and H15 expression is subsequently activated in the same cells. Mutant embryos lacking the activity of mid, or both mid and H15, are able to form dorsal vessels with largely normal numbers of cardioblasts and pericardial cells. Furthermore, the mutant cardioblasts express several general cardioblast markers such as Mef2 and Toll at normal levels. However, the expression of tinman (tin), which normally occurs in four out of six cardioblasts in each hemisegment of the dorsal vessel, is almost abolished. Conversely, the expression of the Dorsocross (Doc) T-box genes, which is normally restricted to the two Tin-negative cardioblasts in each hemisegment, is strongly expanded into the majority of cardioblasts in mid mutant and mid + H15-deficient embryos. Altogether, the data from the loss-of-function phenotypes demonstrate that mid, and to a lesser degree H15, have important roles in establishing the metameric patterning of cardioblast identities, but not in specifying cardioblasts as such. Ectopic expression of mid causes ectopic tin expression and, less efficiently, produces extra cardioblasts. We propose that one of the major functions of mid and HI, 5 during cardioblast development is the re-activation of tin expression at a stage when the induction of tin by Dpp in the dorsal mesoderm has ceased. Through this activity, mid and H15 are required for the normal functional diversification of cardioblasts and the expression of tin-dependent terminal differentiation genes within the dorsal vessel. (c) 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: T-box genes; Tbx20; dorsal vessel; heart development; cardiomyocyte differentiation

The Dorsocross T-box genes are key components of the regulatory network controlling early cardiogenesis in Drosophila - Frasch, Manfred; Reim, Ingolf (Development, 2005)
Cardiac induction in Drosophila relies on combinatorial Dpp and Wg signaling activities that are derived from the ectoderm. Although some of the actions of Dpp during this process have been clarified, the exact roles of Wg, particularly with respect to myocardial cell specification, have not been well defined. Our present study identifies the Dorsocross T-box genes as key mediators of combined Dpp and Wg signals during this process. The Dorsocross genes are induced within the segmental areas of the dorsal mesoderm that receive intersecting Dpp and Wg inputs. Dorsocross activity is required for the formation of all myocardial and pericardial cell types, with the exception of the Eve-positive pericardial cells. In an early step, the Dorsocross genes act in parallel with tinman to activate the expression of pannier, a cardiogenic gene encoding a Gata factor. Our loss- and gain-of-function studies, as well as the observed genetic interactions among Dorsocross, tinman and pannier, suggest that co-expression of these three genes in the cardiac mesoderm, which also involves cross-regulation, plays a major role in the specification of cardiac progenitors. After cardioblast specification, the Dorsocross genes are re-expressed in a segmental subset of cardioblasts, which in the heart region develop into inflow valves (ostia). The integration of this new information with previous findings has allowed us to draw a more complete pathway of regulatory events during cardiac induction and differentiation in Drosophila.
Keywords: mesoderm patterning; heart development; T-box genes; Drosophila

The FGF8-related signals Pyramus and Thisbe promote pathfinding, substrate adhesion, and survival of migrating longitudinal gut muscle founder cells - Reim, Ingolf; Hollfelder, Dominik; Ismat, Afshan; Frasch, Manfred (Developmental Biology, 2012)
Fibroblast growth factors (FGFs) frequently fulfill prominent roles in the regulation of cell migration in various contexts. In Drosophila, the FGF8-like ligands Pyramus (Pyr) and Thisbe (Ths), which signal through their receptor Heartless (Htl), are known to regulate early mesodermal cell migration after gastrulation as well as glial cell migration during eye development. Herein, we show that Pyr and Ths also exert key roles during the long-distance migration of a specific sub-population of mesodermal cells that migrate from the caudal visceral mesoderm within stereotypic bilateral paths along the trunk visceral mesoderm toward the anterior. These cells constitute the founder myoblasts of the longitudinal midgut muscles. In a forward genetic screen for regulators of this morphogenetic process we identified loss of function alleles for pyr. We show that pyr and ths are expressed along the paths of migration in the trunk visceral mesoderm and endoderm and act largely redundantly to help guide the founder myoblasts reliably onto and along their substrate of migration. Ectopically-provided Pyr and Ths signals can efficiently re-rout the migrating cells, both in the presence and absence of endogenous signals. Our data indicate that the guidance functions of these FGFs must act in concert with other important attractive or adhesive activities of the trunk visceral mesoderm. Apart from their guidance functions, the Pyr and Ths signals play an obligatory role for the survival of the migrating cells. Without these signals, essentially all of these cells enter cell death and detach from the migration substrate during early migration. We present experiments that allowed us to dissect the roles of these FGFs as guidance cues versus trophic activities during the migration of the longitudinal visceral muscle founders. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Cell migration; Cell survival; Fibroblast growth factor; Visceral mesoderm; Gut muscle development

The protein Hrb57A of Drosophila melanogaster closely related to hnRNP K from vertebrates is present at sites active in transcription and coprecipitates with four RNA-binding proteins. - Hovemann, Bernhard T.; Reim, Ingolf; Werner, Susanne; Katz, Sylvia; Saumweber, Harald (Gene, 2000)
The hnRNP K protein is among the major hnRNA-binding proteins with a strong preference for cytidine-rich sequences. We have cloned a Drosophila hnRNP protein closely related to this vertebrate protein. The protein first identified by the monoclonal antibody Q18 is encoded by a gene located in 57A on polytene chromosomes and has been consequently named Hrb57A. The amino acid sequence of the Hrb57A KH domains and their overall organisation in the protein are remarkably similar to the vertebrate proteins. As the hnRNP K in vertebrates the M(r) 55 000 Drosophila Hrb57A/Q18 protein strongly binds to poly(C) in vitro and is ubiquitously present in nuclei active in transcription. On polytene chromosomes it is found in many puffs and minipuffs. Hrb57A/Q18 specifically coprecipitates four other proteins: Hrb87F/P11 a Drosophila hnRNP A1 homologue, the hnRNA-binding protein S5, the RNA recognition motif-containing protein NonA and the RNA-binding zinc finger-containing protein on ecdysone puffs PEP/X4.

The puff-specific RRM protein NonA is a single-stranded nucleic acid binding protein. - Reim, Ingolf; Stanewsky, Ralf; Saumweber, Harald (Chromosoma, 1999)
The chromatin protein NonA from Drosophila, present in many puffs on polytene chromosomes, belongs to the growing class of RRM proteins. Exchange of amino acids within the RNP1 and RNP2 consensus sequences, known from other RRM proteins to be essential for RNA binding, has been shown drastically to reduce NonA function in vivo. Here we compare NonA binding to RNA from the Sgs-4 gene, an in situ target for NonA, with binding to Sgs-3 RNA, which is not a target of NonA. Using an immunoprecipitation assay in vitro we show that NonA binds to single-stranded (ss)DNA and RNA with moderate affinity (KD=8x10(-8) M). However, we did not observe sequence-specific binding to the Sgs-4 transcript nor to Sgs-4 DNA containing upstream regulatory sequences. Point mutations within the RNP1 and RNP2 consensus sequences that interfere with NonA function in vivo do not significantly change chromosomal binding nor the general affinity for RNA. The expression of Sgs-4 RNA relative to the expression of Sgs-3 RNA remains the same in the presence or absence of NonA protein. com/link/service/journals/00412/bibs/108n3p162.html

The RNF220 domain nuclear factor Teyrha-Meyrha (Tey) regulates the migration and differentiation of specific visceral and somatic muscles in Drosophila - Frasch, Manfred; Ismat, Afshan; Reim, Ingolf; Raufer, Jasmin (Development, 2023)
Development of the visceral musculature of the Drosophila midgut encompasses a closely coordinated sequence of migration events of cells from the trunk and caudal visceral mesoderm that underlies the formation of the stereotypic orthogonal pattern of circular and longitudinal midgut muscles. Our study focuses on the last step of migration and morphogenesis of longitudinal visceral muscle precursors and shows that these multinucleated precursors utilize dynamic filopodial extensions to migrate in dorsal and ventral directions over the forming midgut tube. The establishment of maximal dorsoventral distances from one another, and anteroposterior alignments, lead to the equidistant coverage of the midgut with longitudinal muscle fibers. We identify Teyrha-Meyhra (Tey), a tissue-specific nuclear factor related to the RNF220 domain protein family, as a crucial regulator of this process of muscle migration and morphogenesis that is further required for proper differentiation of longitudinal visceral muscles. In addition, Tey is expressed in a single somatic muscle founder cell in each hemisegment, regulates the migration of this founder cell, and is required for proper pathfinding of its developing myotube to specific myotendinous attachment sites.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Drosophila; Cell migration; RNF220; Somatic muscle development; Visceral muscle development

The RRM protein NonA from Drosophila forms a complex with the RRM proteins Hrb87F and S5 and the Zn finger protein PEP on hnRNA. - Reim, Ingolf; Mattow, Jens; Saumweber, Harald (Experimental Cell Research, 1999)
The RRM protein NonA, an ubiquitous nuclear protein present in puffs on polytene chromosomes, has been immunopurified as a RNA-protein complex from Drosophila Kc cells. Three other proteins present in the complex have been identified: X4/PEP (protein on ecdysone puffs), a 100-kDa zinc finger RNA-binding protein; the 70-kDa S5 protein, an as yet uncharacterized RNA-binding protein; and P11/Hrb87F, a 38-kDa RRM protein homologous to hnRNP protein A1 from mammals. Monoclonal antibodies against any of the protein components coprecipitate all four proteins although at different ratios. NonA does not coprecipitate with the hrp40 hnRNP proteins and immunolocalizes in a pattern distinct of major hnRNP proteins. Like NonA, X4/PEP, S5, and P11/Hrb87F are present on active sites on polytene chromosomes. The precipitated NonA complex is enriched for certain protein encoding RNAs, notably, histone H3 and H4 RNA.

The T-box-encoding Dorsocross genes function in amnioserosa development and the patterning of the dorsolateral germ band downstream of Dpp - Reim, Ingolf; Lee, Hsiu-Hsiang; Frasch, Manfred (Development, 2003)
Dpp signals are responsible for establishing a variety of cell identities in dorsal and lateral areas of the early Drosophila embryo, including the extra-embryonic amnioserosa as well as different ectodermal and mesodermal cell types. Although we have a reasonably clear picture of how Dpp signaling activity is modulated spatially and temporally during these processes, a better understanding of how these signals are executed requires the identification and characterization of a collection of downstream genes that uniquely respond to these signals. In the present study, we describe three novel genes, Dorsocross1, Dorsocross2 and Dorsocross3, which are expressed downstream of Dpp in the presumptive and definitive amnioserosa, dorsal ectoderm and dorsal mesoderm. We show that these genes are good candidates for being direct targets of the Dpp signaling cascade. Dorsocross expression in the dorsal ectoderm and mesoderm is metameric and requires a combination of Dpp and Wingless signals. In addition, a transverse stripe of expression in dorsoanterior areas of early embryos is independent of Dpp. The Dorsocross genes encode closely related proteins of the T-box domain family of transcription factors. All three genes are arranged in a gene cluster, are expressed in identical patterns in embryos, and appear to be genetically redundant. By generating mutants with a loss of all three Dorsocross genes, we demonstrate that Dorsocross gene activity is crucial for the completion of differentiation, cell proliferation arrest, and survival of amnioserosa cells. In addition, we show that the Dorsocross genes are required for normal patterning of the dorsolateral ectoderm and, in particular, the repression of wingless and the ladybird homeobox genes within this area of the germ band. These findings extend our knowledge of the regulatory pathways during amnioserosa development and the patterning of the dorsolateral embryonic germ band in response to Dpp signals.
Keywords: T-box; amnioserosa; dorsal ectoderm; dpp; Wingless; Drosophila

Twist regulates Yorkie activity to guide lineage reprogramming of syncytial alary muscles - Rose, Marcel; Bartle-Schultheis, Jakob; Reim, Ingolf; Schaub, Christoph; Domsch, Katrin (Cell Reports, 2022)
Genesis of syncytial muscles is typically considered as a paradigm for an irreversible developmental process. Notably, transdifferentiation of syncytial muscles is naturally occurring during Drosophila development. The ventral longitudinal heart-associated musculature (VLM) arises by a unique mechanism that revokes differentiation states of so-called alary muscles and comprises at least two distinct steps: syncytial muscle cell fragmentation into single myoblasts and successive reprogramming into founder cells that orchestrate de novo fiber formation of the VLM lineage. Here, we provide evidence that the mesodermal master regulator twist plays a key role during this reprogramming process. Acting downstream of Drosophila Tbx1 (Org-1), Twist is regulating the activity of the Hippo pathway effector Yorkie and is required for the initiation of syncytial muscle dedifferentiation and fragmentation. Subsequently, fibroblast growth factor receptor (FGFR)-Ras-mitogen-activated protein kinase (MAPK) signaling in resulting mononucleated myoblasts maintains Twist expression, thereby stabilizing nuclear Yorkie activity and inducing their lineage switch into founder cells of the VLM.
CRIS-Team Scopus Importer:2022-02-11
Keywords: FGFR; lineage plasticity; muscle; reprogramming; Twist; Yorkie